2021
DOI: 10.1007/s10342-021-01416-6
|View full text |Cite
|
Sign up to set email alerts
|

A new taper index based on form-factor: application to three bamboo species (Phyllostachys spp.)

Abstract: The form-factor for the stem surface area is directly proportional to the square root of the form-factor for the stem volume, i.e., the square root law of the form-factor. Although the square root law addresses the stems of coniferous trees, the nature of the proportional coefficient of the law has not been discussed. In this study, we demonstrated that the coefficient indicates the stem taper; therefore, it is named “Taper Index based on Form-Factor (TIFF).” We also examined the relationship between the form-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
(74 reference statements)
1
0
1
1
Order By: Relevance
“…Our results showed that the distribution of internode length in P. edulis had distinct features: gradually increasing from the bottom, peaking near the 25th-30th internode, then gradually getting shorter again, showing a shape similar to a Gaussian distribution (Figure 3). These results are in accord with those of recent studies [65], which indicated that the diameter of the internodes gradually decreases from the bottom to the top, becoming extremely thin at the tip; the culm shape is similar to a cone [68,74,75]. P. edulis is generally taller than 10 m, and some individuals reach about 20 m [70][71][72][73]76].…”
Section: Exogenous Treatments Did Not Affect the Characteristics Of T...supporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the distribution of internode length in P. edulis had distinct features: gradually increasing from the bottom, peaking near the 25th-30th internode, then gradually getting shorter again, showing a shape similar to a Gaussian distribution (Figure 3). These results are in accord with those of recent studies [65], which indicated that the diameter of the internodes gradually decreases from the bottom to the top, becoming extremely thin at the tip; the culm shape is similar to a cone [68,74,75]. P. edulis is generally taller than 10 m, and some individuals reach about 20 m [70][71][72][73]76].…”
Section: Exogenous Treatments Did Not Affect the Characteristics Of T...supporting
confidence: 92%
“…Our results show that both Suc and GA had a significant positive effect on the plant height; Suc had a stronger effect on internode number compared with GA, while GA had a stronger effect on internode length than Suc. In addition, we did not find the greater number of internodes (75) or higher plant height (21.0 m) of P. edulis that were published previously [63,[65][66][67][68][69][70][71][72][73][74]. Here, the characteristics of the culm structure, the promoting effects of the exogenous Suc and GA on the plant height, internode length, and internode number, the variation in the effect of exogenous treatment with distance, and the ecological benefits brought by increased plant height are discussed.…”
Section: Discussioncontrasting
confidence: 47%
“…A maneira mais simples e menos usual de determinar a forma a partir do conceito de taper é a partir de um modelo fenomenológico que possui um parâmetro exclusivo de forma. Este modelo proposto por Kunze (1873) apud Inoue et al (2021) associa o raio da seção do tronco (y) em função da distância da seção até a altura total (H − h i ). Possui duas constantes que indicam o afilamento da espécie (α) e outra o expoente de forma (β):…”
Section: Modelos De Taperunclassified